2016
DOI: 10.1186/s40781-016-0113-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of choline chloride supplementation on milk production and milk composition of Etawah grade goats

Abstract: BackgroundThe effect of choline chloride supplementation through forced drinking combined with concentrate diets containing Ca-fish oil on milk production and milk composition of Etawah Grade goats was evaluated. Choline chloride is an essential component in ruminant diets as it is required for fat metabolism.MethodThe experiment was conducted in a completely randomized block design with three types of treatments and eight replications. The trial had two successive experimental periods; the first, during the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
6
1
2
Order By: Relevance
“…The CP intake in this experiment is relatively higher than those reported by Supriyati et al (2016) (148-157 g/d) and by Astuti et al (2019) (129.33-132.08 g/d) for post-weaning EC goats. In this study, the different intakes of CP might be due to the different rations consumed, weight, and age of goats, although the breed was the same with the two previous studies.…”
Section: Intakecontrasting
confidence: 66%
“…The CP intake in this experiment is relatively higher than those reported by Supriyati et al (2016) (148-157 g/d) and by Astuti et al (2019) (129.33-132.08 g/d) for post-weaning EC goats. In this study, the different intakes of CP might be due to the different rations consumed, weight, and age of goats, although the breed was the same with the two previous studies.…”
Section: Intakecontrasting
confidence: 66%
“…Fermentation is one of the ways to improve the quality of the material where in the process there is an overhaul of hard structures physically, chemically and biologically so that the material from complex structures becomes simple, thereby making the digestibility more efficient [17]. According to Oseni and Ekperigin [18], Fermentation of plant waste not only increases the contents of protein, fat or crude fiber, but also increases the content of essential minerals that can be useful to the body's metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Daily average milk yields of SAPERA in this trial were higher compared to milk yield of Etawah Grade goats (Supriyati et al 2016) and lower than milk yield of Saanen goats Zambom et al 2012). Supriyati et al (2016) reported that average daily milk yields of Etawah Grade goat fed with diets containing 12.6% CP and 70.1% TDN during 12 weeks of lactation was 0.678 kg/d.…”
Section: Milk Yieldmentioning
confidence: 57%
“…Supriyati et al (2016) reported that average daily milk yields of Etawah Grade goat fed with diets containing 12.6% CP and 70.1% TDN during 12 weeks of lactation was 0.678 kg/d. However, Gomes et al (2014) reported that average daily milk yields of Saanen goats fed with diets based on soybean meal containing 23% CP during the first 60 days of lactation was 3.29 kg/d.…”
Section: Milk Yieldmentioning
confidence: 99%